PENGARUH KESULITAN PENGUASAAN PERKALIAN DASAR TERHADAP KEMAMPUAN NUMERASI SISWA KELAS IV SDN 104204 SAMBI REJO TIMUR - Hafizah Putri Radinda Br Ginting; Apiek Gandamana; Winara Winara; Syahrial Syahrial; Nur Hudayah (Universitas Negeri Medan, 2026)
Basic multiplication mastery is a fundamental mathematical skill that supports students’ numeracy abilities. However, many elementary school students still experience difficulties in mastering basic multiplication, which may affect their ability to solve numeracy-related problems. This study aimed to determine the effect of difficulties in mastering basic multiplication on the numeracy skills of fourth-grade students at SDN 104204 Sambi Rejo Timur. The study employed a quantitative approach with an ex post facto correlational design. The population and sample consisted of 43 fourth-grade students. Data were collected through multiplication mastery tests, numeracy tests, and documentation. The data were analyzed using normality tests, linearity tests, Pearson Product Moment correlation, t-tests, and coefficient of determination analysis. The results showed a significant effect between basic multiplication mastery and students’ numeracy skills. Students with better mastery of basic multiplication tended to demonstrate higher numeracy abilities. These findings indicate that basic multiplication mastery plays an important role in supporting the development of numeracy skills among elementary school students. Therefore, strengthening students’ mastery of basic multiplication is essential for improving numeracy achievement.